1970
DOI: 10.1001/archinte.1970.00310100114016
|View full text |Cite
|
Sign up to set email alerts
|

Nodular Lymphoid Hyperplasia of the Small Intestine and Sarcoidosis

Abstract: The entire length of the small intestine was studded with myriad 2-to 3-mm no¬ dules which projected into the intestinal lumen (Fig 3). The bowel was not stiff or fixed at fluoroscopic examination. No ste¬ nosis, dilatation, or ulcération was seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1971
1971
1994
1994

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Goldstein et al (1969), in a review of immunoglobin levels in 84 patients with sarcoidosis, mentioned two, both black women, who had no IgA; one, aged 38, had chronic pulmonary sarcoidosis, and the other, aged 39, had BHL with erythema nodosum; in neither was there evidence of undue susceptibility to infections. Davis et al (1970) reported the case of a man, aged 36, who had had recurrent episodes of otitis media and two of pneumonia, and was found to have IgA deficiency; intermittent diarrhoea was assocated with nodular hyperplasia of the lymphoid tissue of the small intestine; ehest radiography showed enlargement of hilar and right paratracheallymph-nodes and rounded shadows in both lower lobes ; biopsy of a scalene lymph-node showed sarcoidtype granulomas; and the hilar lymph-node enlargement and lung shadows subsided spontaneously. Sharma and Chandor (1972) described the case of a 31 year old woman with selective serum and salivary IgA deficiency in whom enlargement of peripherallymph-nodes and lung infiltration was attributed to sarcoidosis, supported by biopsy of a scalene lymph-node.…”
Section: Gammaglobulin Deficiencymentioning
confidence: 99%
“…Goldstein et al (1969), in a review of immunoglobin levels in 84 patients with sarcoidosis, mentioned two, both black women, who had no IgA; one, aged 38, had chronic pulmonary sarcoidosis, and the other, aged 39, had BHL with erythema nodosum; in neither was there evidence of undue susceptibility to infections. Davis et al (1970) reported the case of a man, aged 36, who had had recurrent episodes of otitis media and two of pneumonia, and was found to have IgA deficiency; intermittent diarrhoea was assocated with nodular hyperplasia of the lymphoid tissue of the small intestine; ehest radiography showed enlargement of hilar and right paratracheallymph-nodes and rounded shadows in both lower lobes ; biopsy of a scalene lymph-node showed sarcoidtype granulomas; and the hilar lymph-node enlargement and lung shadows subsided spontaneously. Sharma and Chandor (1972) described the case of a 31 year old woman with selective serum and salivary IgA deficiency in whom enlargement of peripherallymph-nodes and lung infiltration was attributed to sarcoidosis, supported by biopsy of a scalene lymph-node.…”
Section: Gammaglobulin Deficiencymentioning
confidence: 99%
“…The clinical and laboratory findings of these patients are characterized in Table I. Methods for studies summarized in Table I have been published (11)(12)(13). Some of these cases have been reported in part previously; references are cited in the Table. For convenience in presentation, the 26 patients are divided into four groups.…”
Section: New Namementioning
confidence: 99%
“…135-64. 4 Valente PT, Hoober JK, Phillips SJ. Tyrosine-rich crystalloids in pleomorphic adenoma: SEM findings and partial biochemical characterization.…”
mentioning
confidence: 99%